Stress, coping, and psychological resilience among physicians - O’Dowd, Emily (BMC Health Serv Res, 2018)
BACKGROUND: Recent research has demonstrated that burnout is widespread among physicians, and impacts their wellbeing, and that of patients. Such data have prompted efforts to teach resilience among physicians, but efforts are hampered by a lack of understanding of how physicians experience resilience and stress. This study aimed to contribute to knowledge regarding how physicians define resilience, the challenges posed by workplace stressors, and strategies which enable physicians to cope with these stressors. METHODS: A qualitative approach was adopted, with 68 semi-structured interviews conducted with Irish physicians. Data were analysed using deductive content-analysis. RESULTS: Five themes emerged from the interviews. The first theme, ‘The Nature of Resilience’ captured participants’ understanding of resilience. Many of the participants considered resilience to be “coping”, rather than “thriving” in instances of adversity. The second theme was ‘Challenges of the Profession’, as participants described workplace stressors which threatened their wellbeing, including long shifts, lack of resources, and heavy workloads. The third theme, ‘Job-related Gratification’, captured aspects of the workplace that support resilience, such as gratification from medical efficacy. ‘Resilience Strategies (Protective Practices)’ summarised coping behaviours that participants considered to be beneficial to their wellbeing, including spending time with family and friends, and the final theme, ‘Resilience Strategies (Attitudes)’, captured attitudes which protected against stress and burnout. CONCLUSIONS: This study emphasised the need for further research the mechanisms of physician coping in the workplace and how we can capitalise on insights into physicians’ experiences of coping with system-level stressors to develop interventions to improve resilience. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12913-018-3541-8) contains supplementary material, which is available to authorized users.